ANALISIS KESESUAIAN BIAYA RIIL PASIEN KANKER PAYUDARA PESERTA JKN NON-PBI DENGAN TARIF INA-CBG’s DI RSUP PROF DR KANDOU MANADO - Fridly Manawan; Mitra Wynne Timburas (UNIVERSITAS SAM RATULANGI, 2022)
Number of cancer incident in Indonesia exactly in second place that adsorbs state expenditure after hemodialysis included breast cancer. This study aims to find out the suitability of real cost and tariff INA-CBG’s the breast cancer inpatient whom became a member of National Health Insurance (JKN) Non-PBI breast cancer inpatient in RSUP Prof Kandou Manado. The research was an observational study with a cross-sectional design. Data retrospectively collected from medical record inpatient whom registered as a member of National Health Insurance (JKN) Non-PBI during September 2017-August 2018 period and from financial department of RSUP Prof Kandou Manado. Calculating the difference in total real costs with the total tariff of INA-CBG's package in JKN Non-PBI inpatients for breast cancer. The result of the study showed that the cost difference between total real cost and total tariff INA-CBG’s package in chemotherapy patient with C-14-3 code was Rp. 374.645.738, treatment in breast procedure with L-1-50 code was Rp. 496.325.510, and treatment for breast tumor with L-4-11 code was Rp. 294.784.926. The difference value between the real cost and tariff INA-CBG’s package was Rp. 1.165.756.174 for 130 breast cancer patient.